2021
DOI: 10.2147/hiv.s299812
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Discrimination Towards People Living with HIV/AIDS Among People Aged 15–49 Years in Ethiopia: A Multilevel Analysis

Abstract: Background: There is limited national representative evidence on determinants of discrimination towards people living with HIV/AIDS especially, community-level factors that are not investigated in Ethiopia. Thus, this study aimed to assess individual and community-level factors associated with discrimination towards people living with HIV/AIDS among 15-49 age people in Ethiopia. Methods: A secondary data analysis was done on the 2016 Ethiopian Demographic and Health Survey dataset which was collected cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
5
7
2
Order By: Relevance
“…This may be due to the different traditional behaviors and conservative outlooks that aggravate discrimination in regions of SSA Africa. Surprisingly and contrary to different study findings [21,27], the current study revealed that being living in a rural area was associated with lower odds of discriminatory attitude towards people living with HIV/AIDS as compared to those who were from urban areas. This may be due to the advancement of the extension program in remote and rural areas.…”
Section: Plos Onecontrasting
confidence: 99%
See 3 more Smart Citations
“…This may be due to the different traditional behaviors and conservative outlooks that aggravate discrimination in regions of SSA Africa. Surprisingly and contrary to different study findings [21,27], the current study revealed that being living in a rural area was associated with lower odds of discriminatory attitude towards people living with HIV/AIDS as compared to those who were from urban areas. This may be due to the advancement of the extension program in remote and rural areas.…”
Section: Plos Onecontrasting
confidence: 99%
“…The study at hand also revealed that community-level factors such as residence and SSA region were associated with discriminatory attitude towards people living with HIV/AIDS. Consistent with studies conducted elsewhere [21,23,28]; this study also identified regional variations in terms of discriminatory attitude towards people living with HIV/AIDS. This may be due to the different traditional behaviors and conservative outlooks that aggravate discrimination in regions of SSA Africa.…”
Section: Plos Onesupporting
confidence: 88%
See 2 more Smart Citations
“…Discrimination towards PLHA can occur in either urban or rural areas. Previous studies have identified higher discrimination towards PLHA among rural dwellers when compared to urban dwellers [ 27 29 ]. However, in this study, rural dwellers were found to have a lower probability of discrimination towards PLHA when compared to urban dwellers.…”
Section: Discussionmentioning
confidence: 99%